Sistem Pendukung Keputusan dalam Pemilihan Juara Umum pada SMP Negeri 3 Kota Bengkulu - Kanedi, Indra (UNIVED Press, 2018)
As a formal education institution at the first advanced level, SMP Negeri 03 Kota tries to implement all existing computer-based activities, both in terms of preparing subject schedules, making reports and other activities that require the presence of a computer as a tool. To be able to bridge the problems faced by SMP Negeri -3 Bengkulu City in determining the overall class ranking champion for each class increase is to build a program that is built using a programming language. While the method used in the decision making concept is the Simple Additive Weighting (SAW) method, the decision support system (DSS) is a computer-based information system that produces various decision alternatives to assist management in dealing with various structured or unstructured problems using data and models. The benefits of a decision support system are making the right decisions, according to the type of decision required, making forecasts, comparing alternative actions, making impact analyzes and creating models. The SAW method can solve complex problems, where there are quite a lot of criteria taken, the structure of the problem is unclear, the uncertainty of the decision maker's perception and the uncertainty of the availability of accurate statistical data. Bengkulu found that this program really helped the school in selecting the overall champion at the junior high school. Where the process is very fast, practical and objective because the calculations are carried out in the program.